Property Crime with Private Protection: A Market-for-Offenses Approach - Hotte, Louis; Valognes, Fabrice; Ypersele, Tanguy van (Université d'Ottawa | University of Ottawa, 2009)
We analyze property crime in an endowment economy composed of a large number of heterogeneous individuals who need to protect themselves, choose whether to participate in crime or not, and decide on how to allocate their predation efforts across victims. The equilibrium posits perfect foresight by all and the crime payoff clears the market between victims' losses and criminals' gains. We obtain that the crime payoff summarizes all the relevant information concerning the state of the crime environment as far as individual welfare is concerned. The burden of crime, expressed as losses relative to initial wealth, is evenly distributed between rich and poor individuals, inclusive of the protection effort. In absolute terms, the rich spend more on protection and lose more from crime. We derive a necessary and sufficient under which wealth redistribution increases crime. Under a weak sufficient condition, economic development tends to reduce the burden of crime for all, regardless of how its fruits are distributed. The predictions of the model accord well with existing empirical results / Nous analysons le crime contre la propriété en présence d'un grand nombre d'individus dont les niveaux de richesse varient. Chaque individu doit choisir son niveau de protection contre le vol, décider de voler ou non et, le cas échéant, allouer ses efforts de vol entre les victimes. Le concept d'équilibre utilisé suppose une prévision parfaite ainsi qu'un rendement du crime qui assure que les pertes des victimes soient égales aux gains des voleurs. Nous obtenons qu'en ce qui concerne l'individu, le rendement du crime incorpore toute l'information pertinente quant à l'état du crime dans l'économie. À l'équilibre, le fardeau du crime, exprimé en termes relatifs à la richesse initiale, est distribué également entre riches et pauvres, de même que le fardeau de la protection individuelle. En termes absolus, les riches dépenses cependant plus en protection mais se font également voler plus. Nous proposons une condition nécessaire et suffisante pour laquelle une redistribution plus égalitaire de la richesse contribue à hausser le crime. Le développement économique tend à réduire le fardeau du crime pour tous en autant qu'une condition suffisante - mais peu restrictive - soit respectée. Les prédictions du modèle correspondent étonnamment bien aux résultats des études empiriques existantes.
Keywords: Private Protection; Economic Development; Inequality; Protection prive?e; de?veloppement e?conomique; ine?galite?